Agroecology and gender: Level of involvement of women and young people in agroecological farms in the Fatick department - Ba, Aminata; Diakhaté, Finda Bayo; Mané, Cherif A.S.; Gaye, Elhadji Kabe; Piraux, Marc (2024)
This study, which looks at the involvement of women and young people in decision-making on agroecological farms in the Fatick department of Senegal, highlights the importance of these groups in family farming, particularly in agroecological practices. Although women account for the lion's share of food production, they are often relegated to back-breaking tasks and have little influence on strategic farm decisions. They do, however, play a crucial role in seed management, soil conservation and the processing of agricultural products, all activities central to the sustainability of farms. Young people, meanwhile, are often involved in the more physical and technical tasks, and contribute to the emergence of innovations, adopting modern practices such as agroforestry and composting, but are rarely included in strategic decisions. The study shows that, although women and young people are essential to the success of agroecological farms in the Fatick area, their involvement in decision-making remains insufficient, which could act as a brake on the development of agriculture in the Fatick department.